Fast gating in the Shaker K(+) channel and the energy landscape of activation - Sigg, Daniel (National Academy of Sciences, 2003)
An early component of the gating current in Shaker K(+) channels with a time constant of ≈12 μsec has been recorded with a high-speed patch–clamp setup. This fast component was found to be part of the gating current associated with the opening and closing of the channel. With regard to an energy-landscape interpretation of protein kinetics, the voltage and temperature dependence of the fast component may be explained by a combination of drift diffusion and barrier jumping in the initial stages of channel activation. The data were modeled by a gating particle undergoing Brownian motion in a one-dimensional diffusion landscape that featured diminishing electrical resistance and entropy in the direction of channel activation. The final open state of the channel was reasoned to be narrow and deep to account for successful subtraction of linear-charge displacements at positive potentials. The overall picture of gating that emerges from these studies is that the channel experiences incremental organization from a relaxed state in the early steps of activation to a rigidly structured open state.